Educação integral e o paradigma da educomunicação: um estudo sobre o Programa Mais Educação nas escolas de Santa Maria/RS - Nascimento, Maurício Lavarda do (2015)
The More Education Program, established in 2007, came as a strategy of the Brazilian Federal Government to induce the extend of school day and curriculum organization, from the perspective of Integral Education, to improve students learning of public schools by activities inter/transdisciplinary of varied types, among them, communication and digital culture. Given the wide mission and different contexts and realities, we decided to focus in Santa Maria - RS. Therefore, we question: how public schools from Santa Maria - RS appropriate the educommunication to develop the activities of different macrocampos of More Education Program? What are the specifics, identity, of the macrocampo communication and digital culture of Santa Maria schools? (monitor profile, methodologies, themes, devices and processes). To answer these questions, we investigated the appropriation of educommunication by different macrocampos of the More Education Program at Santa Maria - RS, from 2010 to 2014. In addition to this overall objective, we seek to: 1) study the interface between communication and education in the context of public policies in a integral educational perspective; 2) Map the schools that have joined the More Education Program in Rio Grande do Sul State and macrocampos chosen to contextualize the local research; 3) Investigate the development process of More Education Program (profile monitors, methodologies, themes, devices), of the macrocampo Communication and Digital Culture in Schools of Santa Maria / RS; 4) Understand the challenges and opportunities in the development of More Education Program in the schools of the Municipal Network of Santa Maria - RS; 5) Identify whether and how the More Education Program enables the learner empowerment in: cognitive, psychological, cultural and political aspects. To achieve the proposed objectives, we conducted a qualitative and quantitative research at exploratory level (LOPES, 2010). As a method, we choose the case study (FACHIN, 2001). To discuss the epistemology and practice of educommunication and discuss the integral education, we conducted literature (STUMPF, 2011) (re) visiting authors like Soares (1999; 2011a; 2011b, 2014), Moll (2012), Titton and Pacheco (2012 ), Morin (2007), Certeau (2008; 2005; 2003), Santos (2007), Touraine (2006), Kaplun (1998) and Freire (1978; 1983), and also documentary research (FONSECA, 2002) to analytical deepening the object. Related to research techniques, we apply questionnaires semi-open model with semi-structured questions and indeterminate answers (DUARTE, 2011) with coordinators and monitors and conducted in-depth interviews with advisors and students. We also conducted direct observation (Yin, 2005) in five municipal schools in the same city. As a result, we identified the centrality of the subject in the process, both from monitor and coordinator. For despite all the adversities encountered, mainly by lack of infrastructure, most schools are managing to articulate partnerships, develop activities creatively, engage the school community and to overcome the historical and social resistance. Regarding the appropriation of educommunication, we identified that occurs in a creative way, both across the different macrocampos and in particular macrocampo . The main empowerment opportunities identified by research subjects occur in the psychological and cognitive level, with changes in self-esteem and improved student learning. On the other hand, we also found much resistance relative to the More Education Program. These are linked to the lack of infrastructure, cultural shocks caused by the school open to new subjects and changes in school routine. In terms of state responsibility in the development of this public policy it was found the disproportion between available resources and infrastructure in relation to the mission required to increase opportunities, time and educational subjects.